Buddhistisk askese: Fra verdensforsagelse til coping og dannelse - Borup, Jørn (Religionsvidenskabeligt Tidsskrift, 2016)
Asceticism is a central concept in Buddhism. It is both a constituent ideal and a practice needing to be tamed by institutional religion. This article analyzes Buddhist asceticism as textual ideal and religious practice from an understanding of asceticism as both renunciation (Gavin Flood), and training (Peter Sloterdijk). Influenced by Mary Douglas' group/grid model, a typology is suggested in which both the Buddha legend, historical Buddhism in its various expressions and modern Japanese shugyō and Western mindfulness are placed. It is the article's claim that asceticism is a foundational Buddhist ideal and a practice with significance for the development and societal integration of the religion.